Do research studies in the UK reporting child neurodevelopment adjust for the variability of assessors: a systematic review. (26th November 2015) - Khalid, Rahila; Willatts, Peter; Williams, Fiona L R
Abstract : Aim: Neurodevelopment is a key outcome for many childhood trials and observational studies. Clinically important decisions may rest on finding relatively small differences in neurodevelopment between groups receiving complex and costly interventions. Our purpose was to determine whether studies which measure neurodevelopment report the numbers, training, and auditing of assessors and, for multiple assessor studies, whether the results were adjusted and if so by which method? Method: Electronic searches were conducted using Medline, Embase, Cinahl, PsycINFO, and the Cochrane Library. A study was eligible if it reported neurodevelopmental outcome in children resident in the UK, less than or equal to 18 years and was published between 2000 and 2015. Trials and observational studies were included. Results: Three hundred and seven full papers were reviewed: 52% of papers did not report the number of assessors used; 21% used a single assessor; and 27% used multiple assessors. Thirty‐five per cent mentioned that assessors were trained in the use of the neurodevelopmental tool; 13% of assessors were audited; and only 1% of studies adjusted statistically for the number of assessors. Interpretation: At the very least, the quality of reporting the use of assessors in these research publications is poor, while at worst, the variability of assessors may mask the true relationship between an intervention/observation and neurodevelopmental outcome. What this paper adds: UK studies reporting neurodevelopmental outcome inadequately describe how they train and audit assessors. Few studies consider the potential impact on results of using multiple assessors. Very few studies adjust statistically for the number of assessors used. Variability in assessor performance may obscure the true neurodevelopmental status of infants. Researchers should provide evidence of the robustness of their data. This article is commented on by Ansell on page111 of this issue.